Implementasi Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Covid-19 di MTs Istiqlal Deli Tua - Sugiarti Sugiarti (Yayasan Rahmat Islamiyah, 2021)
The general purpose of this research is to find out how to plan, implement and assess / evaluate learning during the Covid-19 pandemic at MTs Istiqlal Delitua. This research is a qualitative research with descriptive methods of research subjects in the field and data obtained from observations, interviews and questionnaires. The implementation of this research began in February-April 2020 with the research subjects being the principal, teachers and students. Planning in the form of carrying out the learning process online, choosing the right application, namely WhatsApp, recording student phone numbers, preparing lesson plans, inserting materials, media and learning methods. Implementation in this learning activity is a preliminary, core activity, assignment. Assessment is seen from the aspect of skills and also knowledge, skill assessment is seen from portfolio assignments and also practice, knowledge assessment is seen from the test results and also exams. Keywords : Covid-19, Pendidikan Agama Islam